Au@Ag core–shell nanoparticles with a hidden internal reference promoted quantitative solid phase microextraction-surface enhanced Raman spectroscopy detection. Issue 38 (3rd May 2017) - Sun, Lei; Zhang, Min; Natarajan, Vinothkumar; Yu, Xiaofei; Zhang, Xiaoli; Zhan, Jinhua
Abstract : Structural representation of the SPME-SERS fiber with an internal reference and the SERS detection. Abstract : The combined applications of solid phase microextraction coupled with surface enhanced Raman spectroscopy (SPME-SERS) detection have been successfully used in environmental analysis. In this work, ZnO nanorods (ZnO NRs) decorated with Au@4-ATP@Ag core–shell nanoparticles (NPs) were fabricated on a stainless steel fiber. The inclusion of an internal reference significantly improved the quality of the quantitative SERS measurements of the analytes. The obtained SERS-active SPME fiber resulted in a better reproducibility of the SERS signals. The relative standard deviation (RSD) value of the SERS-active SPME fiber was found to be 6.7% using malachite green (MG) as a probe molecule. A RSD value of 6.8% was observed when the SERS-active SPME fiber was exposed to laser irradiation continuously for about 10 min. These results suggest that the fiber was prepared with good stability and uniformity. Quantitative SERS measurements of the SERS-active SPME fiber showed an excellent quantitative ability for the detection of MG and crystal violet (CV) in aquaculture water. In CV, the results showed a good linear relationship in the concentration range of 5 × 10 −8 M to 5 × 10 −6 M, and the limit of detection (LOD) can reach 1.9 × 10 −9 M (S/N = 3). This result indicates that the inclusion of an internal reference can effectively correct the signal fluctuation. This work provides versatile detection capability for rapid on-site quantitative SERS detection of different molecular species in environmental media.